2017
DOI: 10.1080/2162402x.2017.1358332
|View full text |Cite
|
Sign up to set email alerts
|

Programmed cell death ligands expression in phaeochromocytomas and paragangliomas: Relationship with the hypoxic response, immune evasion and malignant behavior

Abstract: The hypoxic response underlies the pathogenesis and malignant behavior of PCC/PGL. Regulation of PD-1 receptor-ligand signaling, a therapeutically actionable driver of the anti-tumor immune response, is a hypoxic-driven trait across malignancies. We evaluated the prognostic role of PD ligands in association with biomarkers of hypoxia and angiogenesis in patients with PCC/PGL.Tissue microarrays sections including consecutive cases diagnosed between 1983–2011 were stained for PD-L1 and 2, hypoxia inducible facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 27 publications
3
49
0
Order By: Relevance
“…35 Several antiangiogenic agents, such as sunitinib, pazopanib, axitinib, and cabozantinib, are under investigation. Given that PD-L1/ PD-L2 were expressed in 50% of the tumors surgically removed, 36 NPR of 43% and CBR of 75% in our study, provides a rationale for the development of pembrolizumab for these tumors.…”
Section: Open Accessmentioning
confidence: 73%
“…35 Several antiangiogenic agents, such as sunitinib, pazopanib, axitinib, and cabozantinib, are under investigation. Given that PD-L1/ PD-L2 were expressed in 50% of the tumors surgically removed, 36 NPR of 43% and CBR of 75% in our study, provides a rationale for the development of pembrolizumab for these tumors.…”
Section: Open Accessmentioning
confidence: 73%
“…However, the usefulness of somatostatin analogs in the treatment of patients with PPGLs has not been established, and the clinicopathological value of SSTR IHC should be validated by further studies. Surrogate markers associated with tumor immune microenvironmental factors have been studied recently, especially PD-1/PD-L1 in PPGLs (97,98). Guo et al examined PD-L1 immunoreactivity in 77 PPGL cases using an anti-PD-L1 antibody (clone E1L3N) and reported that 59.74% (46/77 cases) of PPGLs were IHC-positive for PD-L1, with high co-efficiency of Ki-67 LI, as well as the presence of hypertension (97).…”
Section: Newly Proposed Markersmentioning
confidence: 99%
“…In this study, we found that CXCL8 up-regulation is negatively associated with PD-L1 (CD274) and PD-L2 (PDCD1LG2) Meanwhile, we established that the high expression of CXCL8 was positively correlated with the HIF-1α expression. Furthermore, evidence showed that HIF-1α was positively correlated with the expression of PD-L1 and PD-L2 [39,40]. Therefore, we speculated that CXCL8 may play an immunosuppressive function through the HIF-1α/PD-Ls axis.…”
Section: Discussionmentioning
confidence: 89%